(untitled) (Bioscience Journal, 2020)
The evaluation of the physiological potential of sweet corn seeds is fundamental in the production process, because the germination and vigor reflect the potential for storage, commercialization and use of these seeds. The choice of vigor tests with an adequate and efficient analysis methodology is fundamental to obtaining reliable results. In this sense, the objective of this study was to assess the physiological potential of sweet corn seeds after hydration using different moistening methods to increase water content to 20%. First, the lot of seeds was characterized as to its moisture content and initial physiological potential. Subsequently, two experiments were conducted, both under a completely randomized design. In the first experiment, different volumes of water on the filter paper sheets were assessed for seed hydration a method that uses a wet substrate. In the second, four hydration methods were evaluated: wet substrate (WS), humid atmosphere (HU), immersion in water (IW) and addition of the required amount of water (WR). A constant temperature of 25ºC was used in both experiments and then the moisture content and physiological potential of seeds were determined. The humid atmosphere method reduces the physiological quality of sweet corn seeds because it favors the deterioration and hence is unsuitable for the hydration of seeds of this species. The wet substrate method, in an amount equivalent to 2.5 times the paper mass, increased the water content of sweet corn seeds to 20%, achieving the desired degree of moisture without altering their physiological potential.